Reassessing Exegetical Interpretations of Bede’s Historia Ecclesiastica Gentis Anglorum - Rowley, Sharon M. (Literature and theology, 2003)
This essay explores the role of miracles in Bede’s construction of history to argue that, while reading miracles according to Bede’s sense of exegetical history begins analysis, modern scholars should also look beyond the exegetical paradigm to better understand how Bede uses miracles to engage and understand the world. After a brief discussion of Cædmon’s miracle as an example of how miracles ought to work, this essay contrasts Bede’s account of Edwin with his account of Oswald to question Bede’s presentation of Edwin as a saint-king, and to discuss the ways in which these episodes allow us to see Bede, as an historian, at work.